2022
DOI: 10.1017/s0714980822000174
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the Namaste Care Program for Use with Caregivers of Community-Dwelling Older Adults with Moderate to Advanced Dementia: A Qualitative Descriptive Study

Abstract: Family/friend caregivers are highly involved in supporting older adults with dementia who are 65 years of age or older with daily activities, especially when these older adults with dementia are living at home. There is a need for psychosocial interventions for caregivers of older adults with moderate to advanced dementia, as most interventions focus on persons at earlier stages. Namaste Care is a psychosocial, multisensory program intended to enhance quality of life for people with advanced dementia and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 56 publications
(89 reference statements)
2
9
0
Order By: Relevance
“…This study aimed to evaluate the feasibility, facilitators of and barriers to delivering Namaste Care by volunteers and family carers to people with dementia living in their own home. Namaste Care was deemed feasible for Dutch community-dwelling people with mild to severe dementia, in line with a recent study from Canada 28. In general, experiences of family carers and volunteers with Namaste Care were very positive, although some potential drawbacks were identified.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…This study aimed to evaluate the feasibility, facilitators of and barriers to delivering Namaste Care by volunteers and family carers to people with dementia living in their own home. Namaste Care was deemed feasible for Dutch community-dwelling people with mild to severe dementia, in line with a recent study from Canada 28. In general, experiences of family carers and volunteers with Namaste Care were very positive, although some potential drawbacks were identified.…”
Section: Discussionsupporting
confidence: 71%
“… 20 21 This is consistent with companionship being considered one of the most valuable aspects of the Namaste programme in our study and a Canadian study. 28 Various studies have confirmed associations between social interaction and well-being of people with dementia. 34 35 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations